Physics science literacy profile using local wisdom-based instrument and profile of Pancasila students in particle dynamic - Dewi Dewantara; Ismi Fajariah; Zainuddin Zainuddin; Sri Hartini (Universitas PGRI Kanjuruhan Malang, 2025)
The science literacy profile of students in Banjarmasin City has not been fully identified. Therefore, the purpose of this study is to analyse the physics science literacy profile using local wisdom-based instruments and the Pancasila learner profile of high school students in Banjarmasin City. This type of research is quantitative research with purposive sampling technique with a total of 106 students in three high schools in Banjarmasin City. Data were obtained through surveys and analysed descriptively using the Rasch model in the Winstep application. Based on the research, it was found that the science literacy of high school students in Banjarmasin City was categorised as sufficient due to low interest in reading, low analytical skills of students, low knowledge of educators about science literacy, and the lack of evaluation tools that develop science. So it is concluded that the profile of high school physics science literacy in Banjarmasin City is categorised as sufficient.